A technique for interrater reliability evaluation of a mobile game aimed for executive functions stimulation - Cerqueira, Bernardo; Nice Ferrari Barbosa, Debora; Mossmann, João; Barbosa, Jorge (International Journal for Innovation Education and Research, 2019)
This work presents an interrater reliability evaluation of a mobile game aimed for the executive function’s stimulation, specifically the inhibitory control. The educational Exergame “The Incredible Adventures of Apollo & Rosetta in the Space” was presented in a previous piece of work, which showed the development of the game and its application in a researching intervention with children, in the 6 to 10 age-group, in a school environment. Subsequently, the game had its code reworked for being able to be used across different platforms, hence culminating in the present work. The methodology in this paper consists in a mixed qualitative-quantitative evaluation through questionnaires with four domain professionals experienced in the executive functions field. The statistical measurement used was based on the Kappa coefficient and average percentage among the judges. As the results indicate, there was a substantial agreement (k=0,659; P-value=0,000) between the raters, as well as a high percentage of agreement in general on the mobile game’s capability of Executive Functions stimulation for children.